Support Systems of Clinical Decisions in the Triage of the Emergency Department Using Artificial Intelligence: The Efficiency to Support Triage - Karlafti, Eleni; Anagnostis, Athanasios; Simou, Theodora; Kollatou, Angeliki Sevasti; Paramythiotis, Daniel; Kaiafa, Georgia; Didaggelos, Triantafyllos; Savvopoulos, Christos; Fyntanidou, Varvara (Acta medica Lituanica, 2023)
Purpose: In the Emergency Departments (ED) the current triage systems that are been implemented are based completely on medical education and the perception of each health professional who is in charge. On the other hand, cutting-edge technology, Artificial Intelligence (AI) can be incorporated into healthcare systems, supporting the healthcare professionals’ decisions, and augmenting the performance of triage systems. The aim of the study is to investigate the efficiency of AI to support triage in ED.Patients–Methods: The study included 332 patients from whom 23 different variables related to their condition were collected. From the processing of patient data for input variables, it emerged that the average age was 56.4 ± 21.1 years and 50.6% were male. The waiting time had an average of 59.7 ± 56.3 minutes while 3.9% ± 0.1% entered the Intensive Care Unit (ICU). In addition, qualitative variables related to the patient’s history and admission clinics were used. As target variables were taken the days of stay in the hospital, which were on average 1.8 ± 5.9, and the Emergency Severity Index (ESI) for which the following distribution applies: ESI: 1, patients: 2; ESI: 2, patients: 18; ESI: 3, patients: 197; ESI: 4, patients: 73; ESI: 5, patients: 42.Results: To create an automatic patient screening classifier, a neural network was developed, which was trained based on the data, so that it could predict each patient’s ESI based on input variables.The classifier achieved an overall accuracy (F1 score) of 72.2% even though there was an imbalance in the classes.Conclusions: The creation and implementation of an AI model for the automatic prediction of ESI, highlighted the possibility of systems capable of supporting healthcare professionals in the decision-making process. The accuracy of the classifier has not reached satisfactory levels of certainty, however, the performance of similar models can increase sharply with the collection of more data.
Keywords: patient triage; Artificial Intelligence